How Effective Are Non-Operative Intra-Articular Treatments for Bone Marrow Lesions in Knee Osteoarthritis in Adults? A Systematic Review of Controlled Clinical Trials - Alexander C. Kleinschmidt; Ambrish Singh; Salman Hussain; Gregory A. Lovell; Anna Wong Shee (MDPI AG, 2022)
Knee osteoarthritis (KOA) is a progressive joint disease and a leading source of chronic pain and disability. OA-bone marrow lesions (BMLs) are a recognised aetiopathological feature of KOA. Several intra-articular injectable therapies are recommended and used for management of KOA. This systematic review assessed the efficacy and safety of intra-articular therapies for improving OA-BMLs and reducing pain in adults with KOA. The study was conducted following registered review protocol (PROSPERO CRD42020189461) and six bibliographic databases, and two clinical trial registries were searched. We included eight randomised clinical trials involving 1294 participants, reported in 12 publications from 2016 to 2021. Two studies of sprifermin, one of autologous protein solution (APS) and one of high-dose TissueGene-C, reported a positive effect on OA-BMLs under 1-year follow-up. Two studies with corticosteroids reported mixed findings with no beneficial effect beyond 14 weeks of follow-up. One study assessing platelet-rich plasma found no significant improvement in OA-BMLs at 12 months follow-up. Knee pain was improved in two studies evaluating TissueGene-C and one study assessing APS; the remaining studies found no improvement in knee pain. Overall, we found mixed evidence on the efficacy of intra-articular therapy for improving OA-BMLs in KOA. Additional studies with long-term follow-up are needed to confirm the effect of various intra-articular therapies on OA-BMLs in KOA.